2017
DOI: 10.3389/fnins.2017.00317
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Abandoning Therapeutic Chelation of Copper Ions in Alzheimer's Disease

Abstract: The “therapeutic chelation” approach to treating Alzheimer's disease (AD) evolved from the metals hypothesis, with the premise that small molecules can be designed to prevent transition metal-induced amyloid deposition and oxidative stress within the AD brain. Over more than 20 years, countless in vitro studies have been devoted to characterizing metal binding, its effect on Aβ aggregation, ROS production, and in vitro toxicity. Despite a lack of evidence for any clinical benefit, the conjecture that therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 166 publications
(230 reference statements)
1
80
0
Order By: Relevance
“…The beta‐secretase enzyme cleaves the pro‐chelator in a designed site, yielding the XZH motif at the site of Aβ production and a supposed Cu‐induced oxidative stress. On the other hand, a strong critique of the chelation approach to treat Alzheimer's disease was presented recently …”
Section: Applicationssupporting
confidence: 79%
See 1 more Smart Citation
“…The beta‐secretase enzyme cleaves the pro‐chelator in a designed site, yielding the XZH motif at the site of Aβ production and a supposed Cu‐induced oxidative stress. On the other hand, a strong critique of the chelation approach to treat Alzheimer's disease was presented recently …”
Section: Applicationssupporting
confidence: 79%
“…Following the idea, Franz [47] and co-workersd esigned ap rochelator peptidet hat gets activated enzymatically.T he betasecretase enzyme cleaves the pro-chelator in ad esigned site, yieldingt he XZH motif at the site of Ab production andasupposed Cu-induced oxidative stress.O nt he other hand, a strong critiqueo ft he chelation approach to treat Alzheimer's disease was presented recently. [92]…”
Section: Xzh and Xh As Chelators To Remove And/or Redox-silence Cumentioning
confidence: 99%
“…Compounds like clioquinol, believed to deplete copper levels in the body (Cherny et al 2001), were shown to drastically increase the intracellular copper concentration in cells (Treiber et al 2004). Not surprisingly, Drew (2017) concluded that copper ion chelation therapy has not been effective and should be abandoned. Nevertheless, Squitti et al (2017) commented that such therapies have not been fully tested and that a portion of AD patients may benefit.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…[10] Copper ions thus remain a pertinent target for a therapeutic approach,[3d, 5a, 10a, 11] although the first clinical trials along this approach failed to benefit patients. [3d, 12] Targeting Cu ions requires well-defined coordination based approaches and ligand design that is, in general, difficult to include in multi-targeted drug in a first-line strategy. [9a] Hence, we designed the chelating moiety of a drug candidate that could be further implemented towards a multi-targeted purpose.…”
Section: Introductionmentioning
confidence: 99%